Dicer activity in neural crest cells is essential for craniofacial organogenesis and pharyngeal arch artery morphogenesis - Nie, Xuguang (2011)
MicroRNAs (miRNAs) play important roles in regulating gene expression during numerous biological/pathological processes. Dicer encodes an RNase III endonuclease that is essential for generating most, if not all, functional miRNAs. In this work, we applied a conditional gene inactivation approach to examine the function of Dicer during neural crest cell (NCC) development. Mice with NCC-specific inactivation of Dicer died perinatally. Cranial and cardiac NCC migration into target tissues was not affected by Dicer disruption, but their subsequent development was disturbed. NCC derivatives and their associated mesoderm-derived cells displayed massive apoptosis, leading to severe abnormalities during craniofacial morphogenesis and organogenesis. In addition, the 4th pharyngeal arch artery (PAA) remodeling was affected, resulting in interrupted aortic arch artery type B (IAA-B) in mutant animals. Taken together, our results show that Dicer activity in NCCs is essential for craniofacial development and pharyngeal arch artery morphogenesis.